Histomorphology of the hypothalamo-neurosecretory system of the endangered golden mahseer, Torputitora (Hamilton-Buchanan) - Pandey, A K; LaL, K K; Mahanta, P C (Indian Journal of Fisheries, 2011)
Hypothalamus of Tor putitora consist mainly of nucleus preopticus (NPO), nucleuslaterlais tuberis (NLT) and their axonal tracts. NPO is a paired structuretopographically located on either side of the third ventricle anterodorsal to the opticchiasma. Based on size of the neurosecretory cells, NPO is morphologicallydistinguishable into dorsal pars magnocellularis (PMC) comprising larger neuronalcells whereas ventrally situated pars parvocellularis (PPG) is formed of smaller cells.NPO neuronal cells were positive (+) to aldehyde fuchsin (AP) and CAHP but theywere also stainable with acid fuchsin in Mallory's triple stain. A few acid fuchsin+ve neurosecretory globules were also encountered in NPO. NLT neurosecretorycells were large, pleomorphic and distributed uniformly at the floor of the brainclose to the infundibulum. They stained readily with acid fuchsin. Herring bodies(HB) were not observed in the hypothalamo-neurohypophysis of the golden mahseer